51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-900
|View full text |Cite
|
Sign up to set email alerts
|

In-Flight Transition Delay with DBD Plasma Actuators

Abstract: A single dielectric barrier discharge plasma actuator is employed for flow control on the pressure side of a natural laminar flow wing section under free-flight conditions. A full sized motorized glider is equipped with the flow control device and data acquisition hardware to quantify the impact of the actuator on boundary-layer transition. A transition delay of approximately 3% chord is achieved, quantified by microphone and hot-wire measurements. Simultaneously, the influence of the variable ambient conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Successful in-flight transition delay employing a steadily operated single DBD actuator is reported by Duchmann et al, 11 including an estimate of the overall efficiency of the flow control application. Boundary-layer transition on the pressure side of a natural laminar flow (NLF) wing glove is controlled at a flight speed of U ¼ 38 m/s on a motorized glider, rendering the chord Reynolds number Re c ¼ 3 Â 10 6 .…”
Section: Saving Ratementioning
confidence: 87%
See 1 more Smart Citation
“…Successful in-flight transition delay employing a steadily operated single DBD actuator is reported by Duchmann et al, 11 including an estimate of the overall efficiency of the flow control application. Boundary-layer transition on the pressure side of a natural laminar flow (NLF) wing glove is controlled at a flight speed of U ¼ 38 m/s on a motorized glider, rendering the chord Reynolds number Re c ¼ 3 Â 10 6 .…”
Section: Saving Ratementioning
confidence: 87%
“…In the second part (Secs. III-V), the suggested guideline is applied to the experimental data of Kriegseis et al [7][8][9][10] and Duchmann et al, 11 where the consecutive evaluation steps of this guideline are discussed in more detail. For the sake of conciseness, the respective experimental procedures are not presented here in their entirety; only the most relevant details and important results are recapped as a starting point for the present discussions.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental works have evidenced the potential of plasma actuation for delaying transition and extending regions of laminar flow Tropea 2007, 2009;Seraudie, Vermeersch, and Arnal 2011;Duchmann et al 2012;Kurz et al 2012;Duchmann et al 2013). For flat-plate flows, Tropea (2007, 2009) and Duchmann et al (2012) have shown that both continuous and pulsed plasma actuators could delay transition in the presence of zero and adverse pressure gradients.…”
Section: Introductionmentioning
confidence: 97%
“…Hot wire anemometry and stability analyses confirmed that transition was delayed when the actuator was operated. Flight experiments were carried out by Duchmann et al (2013), employing a plasma actuator on the pressure side of a laminar flow wing section test article. Microphone and hot-wire measurements quantified a measurable, but modest amount of transition delay (3% chord).…”
Section: Introductionmentioning
confidence: 99%
“…Their study employed low-velocity wind tunnel testing (between 7 and 15 m s −1 ) and local stability theory to show the transition delay of the flow. Flight tests using continuous plasma actuation [17] also demonstrated a transition delay of 3% of the chord length for a small aircraft (a G109b motorized glider) for a high Reynolds number flow (Re x = u∞x ν ≈ 1.15 × 10 6 ). This work aims to describe the response of a boundary layer flow modified by plasma actuation to incoming TS waves in terms of the relevant physical mechanisms as well as to quantify the growth and decay rates of perturbations over the length of the boundary layer.…”
Section: Introductionmentioning
confidence: 99%